A reading in the history of American television series - KOUAS, Djamel; AMARA, Abdelhalim (Journal of Human Sciences, 2020)
This study attempts to read the historical development of the American television series since its beginning, by focusing on its import stages and the most important factors that contributed and still contribute to its development concerning content and form. In 50s the most important kinds appeared which are still known nowadays. many series were produced such as comedy, policy, western and fiction. This period is followed by the 60s and 70s when not really new form appeared but it witnessed variety and richness in the dramatic content. The 80s and 90s were caracterised by the appearance of magnetoscope and remote control, the number of cable channels has grown considerably, dramatical kinds which are more complex also appeared.